Kenny-Caffey Syndrome Type 2: A Unique Presentation and Craniofacial Analysis. Issue 5 (July 2020) - Turner, Acara E.; Abu-Ghname, Amjed; Davis, Matthew J.; Shih, Linden; Volk, Angela S.; Streff, Haley; Buchanan, Edward P.
Abstract : Abstract: Kenny-Caffey Syndrome Type 2 (KCS2) is a rare genetic disorder characterized by short stature, skeletal dysplasia, primary hypoparathyroidism, and delayed closure of the anterior fontanelle. Patients with KCS2 typically require multidisciplinary management due to numerous craniofacial and skeletal anomalies. Craniosynostosis, however, has not yet been identified in a patient with KCS2 to the best of our knowledge. We present the first case of craniosynostosis in the setting of KCS2 and provide a comprehensive analysis of the associated craniofacial findings to date. The authors will describe the craniofacial features specific to our patient and review the characteristic morphological features in a manner relevant to early recognition and focused evaluation. Abstract : Supplemental Digital Content is available in the text